The ostrich paradox why we underprepare for disasters - Meyer, Robert J. (Robert John); Kunreuther, Howard (Wharton Digital Press, 2017)
We fail to evacuate when advised. We rebuild in flood zones. We don't wear helmets. We fail to purchase insurance. We would rather avoid the risk of "crying wolf" than sound an alarm. Our ability to foresee and protect against natural catastrophes has never been greater; yet, we consistently fail to heed the warnings and protect ourselves and our communities, with devastating consequences. What explains this contradiction? In The Ostrich Paradox, Wharton professors Robert Meyer and Howard Kunreuther draw on years of teaching and research to explain why disaster preparedness efforts consistently fall short. Filled with heartbreaking stories of loss and resilience, the book addresses: How people make decisions when confronted with high-consequence, low-probability events-and how these decisions can go awry; The 6 biases that lead individuals, communities, and institutions to make grave errors that cost lives; The Behavioral Risk Audit, a systematic approach for improving preparedness by recognizing these biases and designing strategies that anticipate them; Why, if we are to be better prepared for disasters, we need to learn to be more like ostriches, not less. Fast-reading and critically important, The Ostrich Paradox is a must-read for anyone who wants to understand why we consistently underprepare for disasters, as well as private and public leaders, planners, and policy-makers who want to build more prepared communities.